Seroprevalence of Markers of Hepatitis B Virus Infection, Associated Factors, and Vaccination Status in Young Adults in Arkhangelsk, Northwest Russia: A Population-Based Cross-Sectional Study - Tatiana Balaeva; Andrej M. Grjibovski; Olga Samodova; Anatoly Sannikov; Elise Klouman (International Journal of Environmental Research and Public Health, 2018)
Russia had a high incidence of hepatitis B virus (HBV) infection before the vaccination campaigns of 1997, 2001, 2007, which targeted newborns, adolescents, and adults, respectively. The aim of our study was to assess the prevalence of serological markers of HBV infection, associated factors, and vaccination status among young adults in Arkhangelsk, Northwest Russia. In this cross-sectional, population-based study, we used a quota sampling method to recruit 1243 adults aged 18–39 years. Participants completed a self-administrated questionnaire and were tested for hepatitis B markers. Associations between positivity for markers and selected sociodemographic and behavioral factors were studied by logistic regression. 10.9% of our participants were positive for at least one marker of hepatitis B, 1.2% were positive for HBsAg, and 42.1% were negative for all markers. In multivariable logistic regression analyses, age 30–34 years; lack of self-reported vaccination; and having ≥2 sexual partners in the last 6 months were associated with positivity for markers of hepatitis B. Hepatitis B vaccination was confirmed in 46.9% of participants. Although half of our study sample was vaccinated, four in 10 were still susceptible to infection and more than one participant in 100 showed evidence of an active infection.